Ottawa releases action plan to implement UNDRIP, despite calls for more consultation | CBC News - Taylor, Stephanie (CBC News, 2023)
The federal government has released its action plan on implementing the United Nations Declaration on the Rights of Indigenous Peoples.
Canada
Keywords: 2023-06 June; United Nations Declaration on the Rights of Indigenous Peoples